Acute distal radial epiphyseal osteomyelitis: a case report. Issue 2 (May 2013) - Allan, C; Huntley, JS
A child developed acute epiphyseal osteomyelitis of the distal radius following a fall. Despite a delay in diagnosis the patient was successfully treated by surgery and antibiotics. Magnetic resonance imaging was the key to the diagnosis and surgical planning.